The causes and consequences of partial prey consumption by wolves preying on moose - Vucetich, John A.; Vucetich, Leah; Peterson, Rolf O. (Behavioral Ecology and Sociobiology, 2012)
For a wide range of taxa, partial prey consumption (PPC) is a frequent occurrence. PPC may arise from physiological constraints to gut capacity or digestive rate. Alternatively, PPC may represent an optimal foraging strategy. Assessments that clearly distinguish between these causes are rare and have been conducted only for invertebrate species that are ambush predators with extra-intestinal digestion (e. g., wolf spiders). We present the first strong test for the cause of PPC in a cursorial vertebrate predator with intestinal digestion: wolves (Canis lupus) feeding on moose (Alces alces). Previous theoretical assessments indicate that if PPC represents an optimal foraging strategy and is not caused by physiological limitations, then mean carcass utilization is negatively correlated with mean kill rate and the utilization of individual carcasses is uncorrelated with time between kills. Wolves exhibit exactly this pattern. We explore how the typical portrayal of PPC by wolves has been not only misleading but also detrimental to conservation by promoting negative attitudes toward wolves.